Numerical simulation of a 5:1 rectangular cylinder at non-null angles of attack. Issue 151 (April 2016) - Patruno, L.; Ricci, M.; de Miranda, S.; Ubertini, F.
Abstract: In this paper, the flow around a rectangular cylinder with aspect ratio 5:1 is studied at three attack angles by means of both LES and URANS simulations. Despite its geometric simplicity, such a rectangular shape is characterized by many aerodynamic phenomena typical of reattached flows around bluff bodies and has been recently widely studied as a prototype of flows encountered around shapes of technical interest like, for example, bridge deck sections. The present study is aimed at providing insight in the modifications occurring in the flow at small incidence angles, by comparing the accuracy of the two aforementioned simulation strategies in reproducing them. Some recurring biases observed in URANS simulations are illustrated and their origin discussed. Results are presented in terms of flow bulk parameters and pressure distributions and systematic comparison with available experimental data is provided. Finally, the effects of small incidence angles on along span flow correlations are investigated and Covariance Proper Transformation is used in order to further characterize the flow dynamic behavior. Abstract : Highlights: The flow around a 5:1 rectangular cylinder is simulated at non-null attack angle. Results obtained by using RANS and LES models are compared. Some biases induced by the adoption of RANS models are identified. CPT decomposition is used to extract the main features of the flow dynamics.